Exhibition - Mussorgsky, Modest Petrovich 1839-1881; Ravel, Maurice 1875-1937 (ZDF, 2016)
Star choreographer Sidi Larbi Cherkaoui and rising talent Jeroen Verbruggen create groundbreaking new choreographies to works composed and arranged by the beloved French composer Maurice Ravel at the Royal Ballet Flanders. Maurice Ravel has been an inspiration to artists of all stripes for more than a century. In this filmed performance featuring the Royal Ballet and Opera Orchestra of Flanders, his music is brought to life through human movement. First comes Exhibition, a choreography by Sidi Larbi Cherkaoui set to Ravel's orchestration of Modest Mussorgsky's Pictures at an Exhibition. Then his collaborator Jeroen Verbruggen, winner of the Prix de Lausanne, set the composer's Ma mère l'Oye
Keywords: Ballets; Filmed ballets; Internet videos